2017
DOI: 10.1002/jcu.22528
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal diagnosis and management of oropharyngeal fetus in fetu: A case report

Abstract: Fetus in fetu is an extremely rare congenital anomaly. We describe the perinatal diagnosis and management of a fetus with oropharyngeal and cervical fetus in fetu. High-resolution ultrasonography with 3-dimensional rendering can identify increased risks of airway obstruction in utero. Early identification allows a multidisciplinary team to be assembled for a scheduled ex utero intrapartum treatment procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
6
0
2
Order By: Relevance
“…FIF mostly located within the abdomen (80%), skull (8%) and sacral region (8%) [4]. The location of oral/ oropharyngeal was only reported in two prenatal cases [7, 8]. Although the mass in FIF was benign, it may compress surrounding tissues and cause destructive lesions and maldevelopment of surrounding organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FIF mostly located within the abdomen (80%), skull (8%) and sacral region (8%) [4]. The location of oral/ oropharyngeal was only reported in two prenatal cases [7, 8]. Although the mass in FIF was benign, it may compress surrounding tissues and cause destructive lesions and maldevelopment of surrounding organs.…”
Section: Discussionmentioning
confidence: 99%
“…For cranial FIF, obstructive hydrocephalus and mental retardation may be associated. For thoracic FIF, dysphagia and even airway obstruction may occur and therefore emergency surgery is needed [7, 8]. Also, for FIF with multiple or large mass, or with abundant blood supply, heart failure and hydrops is the associated risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutisch kommen chirurgische Maßnahmen sowie Radio-und Chemotherapie zum Einsatz. Bei den HIV-assoziierten und iatrogenen Formen wird zudem eine (soweit möglich) Wiederherstellung der Immunkompetenz angestrebt [212].…”
Section: Weichteilsarkomeunclassified
“…Their prevalence amounts to about 5 or 2%, respectively 2 . An extreme form of a remnant from the embryonic stage is the extremely rare occurrence of an immature twin within the more mature twin ( fetus in fetu ) in the neck area for which only few case reports have been published 207 213 . More frequently, the congenital or acquired misalignment of the neck called torticollis is observed that affects about 0.5% of the population and thus it is not an orphan disease according to the definition 51 .…”
Section: Cervical Soft Tissuesmentioning
confidence: 99%